Alpha-ketoglutarate mediated hepatoprotection against alcohol induced toxicity: in vivo functional observation studies in Sprague Dawley rats using gamma scintigraphy. (2nd September 2020) - Mehra, Lalita; Rawat, Harish; Jaimini, Abhinav; Tyagi, Amit; Mittal, Gaurav
Abstract: Alcohol is the most abused psychoactive substance and known hepatotoxicant. Present study elucidates possible therapeutic effect of oral alpha-ketoglutarate (AKG) supplementation against alcohol induced hepatic dysfunction, using biochemical, histopathological and most importantly, in vivo functional imaging approaches. Animals were divided into three groups of 6 animals each. Group-I (control): Normal saline; Group-II: 20% (v/v) solution of ethanol (5 ml/day) intragastrically using oral gavage for 2 months. Group-III: ethanol treatment as in group-II along with AKG supplementation (2g/kg/bw; intragastrically using oral gavage for 2 months). In vivo hepatobiliary scintigraphy was performed in all animals using 99m Tc-mebrofenin ( 99m Tc-MEB) as radiotracer to determine changes in (a) Hepatic extraction fraction (HEF), for quantification of radiotracer uptake, (b) Time to reach maximum hepatic uptake (Tpeak ), and (c) Time for hepatic uptake to reduce by 50% (T1/2peak ). Biochemical (alanine aminotransferase, aspartate aminotransferase, reduced glutathione, superoxide dismutase, catalase, and lipid peroxidation) and histological parameters were also studied. Hepatic uptake and excretion kinetics using 99m Tc-MEB scintigraphy showed prompt 99m Tc-MEB clearance from liver in control group (HEF: 91.26 ± 2.32; Tpeak : 143 ± 23 sec; T1/2peak : 434 ± 41 sec), while it was significantly abnormal in ethanol group and showed less efficient radiotracer accumulation (HEF: 62.72 ± 5.6; Tpeak : 201 ± 33 sec; T1/2peak : 542 ± 52 sec). Supplementation of AKG along with ethanol significantly improved liver function (HEF: 76.42 ± 5.3; Tpeak : 155 ± 34 sec; T1/2peak : 455 ± 22 sec). Biochemical and histopathology parameters were correlative to findings of functional imaging study. Results strongly indicate hepatoprotective potential of AKG against alcohol-induced hepatic injury. Study further proposes the use of in vivo hepatobiliary scintigraphy for high throughput screening of other hepatoprotectants.